El desarrollo humano integral. Horizonte de formación por capacidades y competencias. La gestión del proyecto institucional universitario (2016)
This reflection article outlines the concerns and interpretations that emerge in the daily communicative praxis about the crisis of the university, its effects on society, and possible alternative solutions not only from science, technology or global market, but also from the wide horizon of the humanities. It is assumed that philosophy has exceeded the office of “settler”, fixing boundaries and checking the roles that the “cognitive-instrumental, practical-moral and aesthetic expressive” should play, mediating the debate between them. The crisis of the university is located in the wider horizon of the crisis of modernity, as a result of the fracturing of the emancipatory rationality and positioning of the economic reason against the ethical-political subject.Methodology: In this article, the author analyzes the Higher Education System inherited from the Enlightenment Modernity and assimilated by the current cultural Colombian ethos, inasmuch as what medieval universities gave to current higher education institutions is recognized, specially concerning the holistic and corporate approach of novelties in their times, such as the Aristotelian legacy. From the Latin American context, among other references, the author takes into account the reports from institutions such as UNESCO, ECLAC and independent institutions devoted to the study of the qualification of higher education in Latin America. In the Colombian case, the author reflects on the study of the fundamental human rights traced by the Constitution of 1991 and the Act 30 from 1992.Results and conclusión: The author proposes the human development focus as the possible horizon for the Education based on skills and competences, enriched by the findings of Martha Nussbaum. Reflecting on the choices for strengthening the personalized approach, the author articulates the responsive pedagogy proposed by J.J. Sedano and the comprehension approach by Bernard Lonergan, both of which are emphatic in the centrality of the subject formed in a concrete reality and in order to respond consciously to the needs of a historical context. From a hermeneutical and pragmatic perspective, the author invites to inquire on the new foundations of the higher education proposal, aiming at its pertinence to the needs of people nowadays.